2017
DOI: 10.1016/j.enconman.2017.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of urban form on the performance of road pavement solar collector system: Symmetrical and asymmetrical heights

Abstract: 3Recent works have highlighted the importance of mitigating the urban heat island effect using 4 innovative technologies. Several studies have emphasised the capabilities of the road pavement solar 5 collector system to dissipate high temperature from the pavement/road surfaces not only to expand its 6 lifecycle but also to reduce the Urban Heat Island effect. This study builds on previous research 7 combining an urban configuration and a road pavement solar collector system in Computational Fluid 8Dynamics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Other papers on the efficient waste management regard the definition of a primary energy return index, used for comparing different municipal solid waste management scenarios [49]; the coupling of renewable energy source in a wastewater treatment plant consisted of conventional activated sludge systems [50]; and a novel methodology applied to evaluate urban wastewater treatment plants in terms of energy efficiency [51,52]. This topic was dealt with comprehensively in previous SDEWES SIs focusing on different aspects, namely: the influence of urban form on the performance of road pavement solar collector system [53]; the energy management in a smart municipal energy grid including combined heat and power plants, solar photovoltaic and wind technologies [54]; the analysis of the future energy scenarios on the Danish municipality of Helsingør to obtain a cost-optimal combination between individual heating, district heating and heat savings [55]; a study on the management of dust to ensure that urban environment and industry can coexist in a sustainable and beneficial manner [56]; the adoption, in urban water distribution systems, of energy storage systems to meet the water demand [57]; the evaluation of carbon emissions in highly polluted European cities [58]; the replacement of bituminous roofs as green roofs to make cities more 'future proof' and resilient [59]; the integration of the renewable energy resources to enhance the regional energy efficiency and sustainability [60]; and many other papers concerning the analysis of energy efficiency targets of the member countries of the EU [61][62][63].…”
Section: Topic Methodology Main Outcomesmentioning
confidence: 99%
“…Other papers on the efficient waste management regard the definition of a primary energy return index, used for comparing different municipal solid waste management scenarios [49]; the coupling of renewable energy source in a wastewater treatment plant consisted of conventional activated sludge systems [50]; and a novel methodology applied to evaluate urban wastewater treatment plants in terms of energy efficiency [51,52]. This topic was dealt with comprehensively in previous SDEWES SIs focusing on different aspects, namely: the influence of urban form on the performance of road pavement solar collector system [53]; the energy management in a smart municipal energy grid including combined heat and power plants, solar photovoltaic and wind technologies [54]; the analysis of the future energy scenarios on the Danish municipality of Helsingør to obtain a cost-optimal combination between individual heating, district heating and heat savings [55]; a study on the management of dust to ensure that urban environment and industry can coexist in a sustainable and beneficial manner [56]; the adoption, in urban water distribution systems, of energy storage systems to meet the water demand [57]; the evaluation of carbon emissions in highly polluted European cities [58]; the replacement of bituminous roofs as green roofs to make cities more 'future proof' and resilient [59]; the integration of the renewable energy resources to enhance the regional energy efficiency and sustainability [60]; and many other papers concerning the analysis of energy efficiency targets of the member countries of the EU [61][62][63].…”
Section: Topic Methodology Main Outcomesmentioning
confidence: 99%
“…The work (Nasir et al, 2017a) investigated the influence of pipe layout, embedded pipe depth, pipe spacing, pipe diameter, the flow rate of the medium used for the heat transfer, thermal conductivity, etc. The impact of building geometry (Nasir et al, 2015) and street canyon aspect ratio (Nasir et al, 2017c, Nasir et al, 2017b) on the PSC system performance were also analysed using a decoupled approach. The decoupled approach simulates the urban canyon and PSC system separately and cannot predict the PSC's direct influence on the urban air temperature.…”
Section: Novelty and Gaps In Knowledgementioning
confidence: 99%
“…The environmental parameters would also affect the performance of pavement solar collectors. The influence of building geometry, urban street canyon aspect ratio and urban form on the PSC system have been analysed in the previous works (Nasir et al, 2015, Nasir et al, 2017c, Nasir et al, 2017b. Memon et al (2010) evaluated the role of wind speed and building aspect ratio (ranging between 0.5 and 8) on air temperatures in an urban canyon using CFD and comparing results with wind tunnel measurements; two diurnal and one nocturnal heating situation were considered.…”
Section: Introductionmentioning
confidence: 99%
“…In their extended work, the ASC system was optimized in terms of pipe diameter, pipe depth, water velocity, and water temperature, for both urban and rural domains. Further, they analyzed the effect of urban form (symmetric and asymmetric height of the urban street canyon) on the performance of ASC and found that there was a significant reduction in the ASC performance when taller building row was behind the first approaching building row. Also, study on the effect of canyon aspect ratio showed that there was significant increase of pavement surface temperature when the aspect ratio was increased from 1 to 2 beyond which there was only minimal increase.…”
Section: Technologies Of Energy Harvesting From Pavements and Roadwaysmentioning
confidence: 99%